'I Was a Tape Recorder. I Was a Mailing Box.': Jan Karski's Interviews. Issue 4 (1st October 2020) - Skorczewski, Dawn; Stone, Dan
ABSTRACT: Jan Karski, a courier for the Polish government in exile, secretly entered the Warsaw ghetto and transit camp Izbica to observe the suffering there. Making a careful record of his visit, he traveled the world to tell its leaders what he had witnessed. Karski is one of the most significant witnesses of the Holocaust, whose experiences have been documented innumerable times. To date, however, no comparative study exists of Karski's interviews. To what extent do Karski's versions of his heroic story differ? Does it matter? What does this case teach us about Holocaust 'celebrity witnessing'? In this article, we trace shifts in a well-known Holocaust narrative to illustrate how even a very well-established story, divided into three well-established smaller stories, changes significantly depending on the archiving institution that collects the account and the interviewers who conduct each interview. Our investigation demonstrates the effects of the archive on oral testimony and narrative history. These effects are always part of the oral testimony setting, but in the case of well-known interviewees such as Karski, who have testified a number of times in different contexts, they are especially evident. Conducted over a seventeen-year period in very different institutional and generic settings, Karski's testimonies illustrate both internal heterogeneity, integral to his own development as a person, an intellectual, and a witness, and 'external' heterogeneity, shaped by the interviewing institution and the interviewer's methodology. We study the production of Karski's interviews from 'the contact zone' of Holocaust testimony to identify how the details of his story shift in relation to his listener. Although it has been suggested that Karski's 'performances' become more wooden over time, we find the opposite: that he becomes more animated, sure of himself, and, by the time of his last interview, ready to fully inhabit the role of the 'celebrity witness.'